2007
DOI: 10.1093/jjco/hym138
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Therapy for Recurrent Esophageal Cancer after Surgery: Clinical Results and Prognostic Factors

Abstract: The prognosis of patients with post-operative loco-regional recurrence of esophageal cancer is poor. However, a long-term survival may be expected by definitive radiotherapy for the patients with small-size tumors and with a good PS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 15 publications
3
56
1
Order By: Relevance
“…Improvement of symptoms with an objective response rate of 65-91% has been reported in several studies [5,15,16]. In our study, an objective improvement of symptoms was observed in 68% of patients, which is in line with other reports.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Improvement of symptoms with an objective response rate of 65-91% has been reported in several studies [5,15,16]. In our study, an objective improvement of symptoms was observed in 68% of patients, which is in line with other reports.…”
Section: Discussionsupporting
confidence: 93%
“…Nemoto et al [16] reported that 1 patient (3%) died of necrosis of the gastric tube 6 months after an RT dose of 66 Gy. Shioyama et al [5] observed no significantly survival difference between the REC patients treated with 60 Gy or more and those treated with less than 60 Gy (p = 0.10), but a significant difference between doses <50 Gy and ≥ 50 Gy (p = 0.04). In our series, patients who were treated with conformal RT had a longer survival compared to those with conventional plan.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Factors such as the time to recurrence, number of recurrent tumors, tumor size, presence of distant organ recurrence, the administration of preoperative therapy and lack of treatment for recurrence have been reported to be risk factors for a dismal post-recurrence survival [9][10][11][12][13] . In this study, we investigated the value of these factors in predicting the prognosis after recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…However, long-term survival might be expected by definitive radiotherapy for the patients with small-size tumors and with a good performance status [25] . Raoul et al [26] reported the survival rates of patients with postoperative recurrence treated with chemoradiotherapy to be 47.1% at one year, 17.1% at two years and 4.3% at three years.…”
Section: Discussionmentioning
confidence: 99%